(untitled) (European Journal of Pure and Applied Mathematics, 2023)
Groundwater plays an important role in feeding many families and societies whose access to water is a huge problem for several reasons, then the mathematical model is an essential part of a hydrologist’s daily life to understand the physical phenomena. In this paper, we used Dupuit’s assumption to reduce the groundwater flow equation and integrated vertically it to obtain the diffusivity equation in terms of the hydraulic head, further, the introduction of fundamental ideas in groundwater research, including vocabulary and mathematics will give readers the basis knowledge. Numerous numerical techniques can be recognized, the unstructured finite volume method was used to solve a transient diffusivity equation through a coastal confined aquifer. The constructed finite volume schemes are used to study the distribution of hydraulic heads in the model domain, to determine water table fluctuations, and to predict the drawdown phenomena.